2021
DOI: 10.2147/jir.s316177
|View full text |Cite
|
Sign up to set email alerts
|

Combining Preoperative and Postoperative Inflammatory Indicators Can Better Predict the Recurrence of Hepatocellular Carcinoma After Partial Hepatectomy

Abstract: Previous studies have shown that various preoperative inflammatory indicators can predict the prognosis of hepatocellular carcinoma (HCC), but the role of postoperative inflammatory indicators remains unclear. This study aimed to explore the prognostic value of postoperative inflammatory indicators and whether combining preoperative and postoperative inflammatory indicators can improve the predictive performance of the prognostic model. Patients and Methods: Eighty-eight patients with primary HCC were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(65 reference statements)
0
3
0
Order By: Relevance
“… 16 Indeed, postoperative inflammatory indicators, such as postoperative platelet–lymphocyte ratio (PostPLR) and postoperative neutrophil–lymphocyte ratio (PostNLR), can greatly affect HCC prognosis. 17–19 Various postoperative inflammatory indicators have been linked to the long-term prognosis of patients with different solid tumors. 20 , 21 For instance, PostNLR has been identified as an independent prognostic factor of survival in patients with small HCC undergoing radiofrequency ablation.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Indeed, postoperative inflammatory indicators, such as postoperative platelet–lymphocyte ratio (PostPLR) and postoperative neutrophil–lymphocyte ratio (PostNLR), can greatly affect HCC prognosis. 17–19 Various postoperative inflammatory indicators have been linked to the long-term prognosis of patients with different solid tumors. 20 , 21 For instance, PostNLR has been identified as an independent prognostic factor of survival in patients with small HCC undergoing radiofrequency ablation.…”
Section: Introductionmentioning
confidence: 99%
“…A 2018 study on postoperative NLR predicting prognosis and recurrence of HCC after resection showed that postoperative NLR ≥ 2.29 indicated poor prognosis, postoperative NLR ≥ 2.41 indicated early recurrence, and NLR ≥ 2.15 indicated late recurrence 46 . Recent studies have found that postoperative NLR can better predict DFS after hepatectomy, and the prognostic model combining preoperative and postoperative NLR improved the prediction performance, which is better than the Barcelona Clinic Liver Cancer staging 47 . Based on these studies, future studies on prognostic prediction models after hepatectomy should pay more attention to postoperative inflammatory indicators or the combination of multiple inflammatory indicator models.…”
Section: Role Of Inflammation In Recurrence Of Hcc After Curative Res...mentioning
confidence: 98%
“…46 Recent studies have found that postoperative NLR can better predict DFS after hepatectomy, and the prognostic model combining preoperative and postoperative NLR improved the prediction performance, which is better than the Barcelona Clinic Liver Cancer staging. 47 Based on these studies, future studies on prognostic prediction models after hepatectomy should pay more attention to postoperative inflammatory indicators or the combination of multiple inflammatory indicator models.…”
Section: Neutrophil-to-lymphocyte Ratio and Platelet-to-lymphocyte Ratiomentioning
confidence: 99%